PENGARUH KEPEMIMPINAN TRANSFORMASIONAl, KOMPETENSI TIK, DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN TAMIANG HULU ACEH TAMIANG - Adi Suria Darma; Hera Yanti; Munawar Munawar (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze the influence of transformational leadership and information and communication technology (ICT) competence on teacher performance, with work motivation as a mediating variable. The research is grounded in the importance of improving teacher performance as a key pillar in enhancing the quality of education, particularly in geographically and infrastructurally disadvantaged areas such as Tamiang Hulu Subdistrict. The study employed a quantitative approach using path analysis, which allows for the examination of both direct and indirect relationships among variables in a comprehensive manner. Data were collected through questionnaires distributed to elementary school teachers and analyzed using statistical software. The results show that transformational leadership and ICT competence significantly affect work motivation. In turn, work motivation has a significant impact on teacher performance and effectively mediates the relationship between transformational leadership and teacher performance. While the direct effect of transformational leadership on performance is not statistically significant, its indirect effect through work motivation is proven to be significant. Conversely, ICT competence has both direct and indirect significant effects on teacher performance. The model evaluation indicates a good fit, demonstrated by an R² value of 0.726, a significant F-test (p < 0.001), mostly significant path coefficients, and low residual values. These findings support established theories such as Bass (1985) on transformational leadership, Davis (1989) on the Technology Acceptance Model (TAM), and Herzberg (1959) on work motivation. This study contributes theoretically by integrating the three main variables into a single structural model, and practically by offering a holistic approach to developing strategies for improving teacher performance. The implications highlight the importance of synergy between school principals' leadership styles, teachers’ technological competence, and internal motivational drives in achieving optimal work performance. Limitations include the study’s narrow geographic scope and reliance on self-reported data. Nonetheless, these findings provide a strong foundation for future research and the formulation of relevant educational policies, especially in remote areas..